Vera Rubin : a life - Mitton, Jacqueline; Mitton, Simon, 1946- (Harvard University Press, 2021)
"Jacqueline Mitton and Simon Mitton offer the first biography of Vera Rubin, an astronomer who made vital contributions to our understanding of dark matter. An outstanding scientist herself, Rubin also championed women in science, by mentoring, advocating for hiring women faculty, disseminating their research, and recognizing their achievements"--